Learning from experience: does providing end-of-life care support for relatives boost personal end-of-life health literacy? - Clément Meier; Maud Wieczorek; Sarah Vilpert; Carmen Borrat-Besson; Ralf J. Jox; Jürgen Maurer (BMC Palliative Care)
Abstract Background Despite the critical role of health literacy in utilizing palliative care and engaging in advance care planning, limited research exists on the determinants of end-of-life health literacy. This study investigates the association between individuals’ experiences with end-of-life care support to relatives and their end-of-life health literacy among a population-based sample of adults aged 58 and older. Method We used data from 1,548 respondents in Switzerland to Wave 8 (2019/2020) of the Survey on Health, Ageing, and Retirement in Europe. Their ability to understand medical jargon, find information, communicate, and make decisions about end-of-life care options was measured with the validated Subjective End-of-Life Health Literacy Scale. Experiences with end-of-life care support include having made medical decisions as healthcare proxy, accompanied, or cared for relatives at the end of life. Associations were estimated using ordinary least squares regressions, controlling for socio-demographic, health, and regional characteristics. Results Respondents who experienced being a healthcare proxy (p < 0.001), who accompanied (p < 0.001), or who cared for a relative at the end of life (p < 0.001) tended to have higher levels of end-of-life health literacy. These results remained significant when the three variables were simultaneously included in the multivariable model (p < 0.001, p < 0.001 and p < 0.05). Conclusions Our findings suggest that providing end-of-life care support to relatives is associated with higher end-of-life health literacy. Thus, as caregivers gain experience caring for others, targeted interventions could leverage their skills and encourage them to think of engaging in end-of-life planning for themselves.